Interactions between stearic acid and calcite surfaces: Experimental and computer simulation studies. Issue 3 (26th July 2021) - Zhang, Lihua; Liu, Laibao; Li, Xiaopeng; Tang, Youhong; Liu, Chuanbei; Zhang, Hong‐Ping
Abstract: Calcite surface was modified with stearic acids, and the interaction between them was investigated both experimentally and theoretically. Stearic‐acid‐modified calcite powders were investigated with Fourier transform infrared spectroscopy, X‐ray diffraction, zeta potential analyser and contact angle measurement. Then, the density functional theory calculations were performed to explore the interaction at the atomic scale. The experimental results and simulation indicated that stearic acids interact with calcite surface via chelation between the double‐bond O atom of –COOH and the Ca atom on calcite surface. The terminal methyl group of the stearic acids decreases the hydrophilicity of the calcite surface, and the interaction between different crystal faces of calcite is different.